2009
DOI: 10.1167/9.9.11
|View full text |Cite
|
Sign up to set email alerts
|

The discrimination of chromatic textures

Abstract: Color discrimination is influenced by chromatic distributions such as they appear on differently illuminated 3D surfaces (T. Hansen, M. Giesel, & K. R. Gegenfurtner, 2008). Here, we measured discrimination thresholds for chromatically variegated stimuli and modeled the data employing a model with multiple chromatic mechanisms. Each mechanism has a differently tuned half-wave-rectified cosine-shaped sensitivity profile centered at a different chromatic direction. To estimate thresholds, the model's responses to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…This might have appeared as the CP differences between the conditions, even if the same mechanisms process both the conditions. The idea that a common mechanisms model subserved the near and away conditions is consistent with the results of Giesel et al 22) Note that the CI experiment simulations based on our optimized models showed that the optimized model could not completely replicate the observer's responses. For example, about 0.2 distances in the isoluminant plane remained between the observer's CP and the model's CP.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This might have appeared as the CP differences between the conditions, even if the same mechanisms process both the conditions. The idea that a common mechanisms model subserved the near and away conditions is consistent with the results of Giesel et al 22) Note that the CI experiment simulations based on our optimized models showed that the optimized model could not completely replicate the observer's responses. For example, about 0.2 distances in the isoluminant plane remained between the observer's CP and the model's CP.…”
Section: Discussionsupporting
confidence: 88%
“…Recently, the color discrimination sensitivities for colors away from an adaptation color for heterochromatic stimuli have also been investigated. 21,22) For example, Giesel et al 22) reported elongation of the discrimination threshold contours similar to those observed in Sankeralli and Mullen 20) for multicolored texture stimuli whose color distribution center was located at or away from an adaptation color. Moreover, a model with eight chromatic mechanisms provided a better fit to these elongations than a four-mechanism model or the cardinal mechanisms model.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Recent findings from neuroimaging studies suggest that the cerebral processing of form, texture, and color may be independent. 24,25 Yet, these studies provide no answer to the question how those object features interact when subjects have to respond on emotion scales.…”
Section: Discussionmentioning
confidence: 99%